2019
DOI: 10.3847/1538-3881/ab46c0
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Constraints for Lucy Mission Trojan Asteroids via Near-infrared Spectroscopy

Abstract: We report near-infrared (0.7-2.5 µm) reflectance spectra for each of the six target asteroids of the forthcoming NASA Discovery-class mission, Lucy. Five Jupiter Trojans (the binary (617) Patroclus system, (3548) Eurybates, (21900) Orus, (11351) Leucus, and (15094) Polymele) are well-characterized, with measurable spectral differences. We also report a survey-quality spectrum for main belt asteroid (52246) Donaldjohanson. We measured a continuum of spectral slopes including "red" (Orus, Leucus), "less red" (Eu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…In the case of the Jovian Trojans, simulations of hypothetical objects have indicated that at small sizes (<1 km), the Yarkovsky effect could impact the stability of the objects (Wang & Hou 2017;Hellmich et al 2019). As we are simulating known Jovian Trojans, the majority of the objects are greater than several kilometres in size (Emery et al 2015), and have unknown or highly uncertain thermal properties (Slyusarev & Belskaya 2014;Sharkey et al 2019). For these reasons, we have not included the Yarkovsky effect in our simulations.…”
Section: E T H O D Smentioning
confidence: 99%
“…In the case of the Jovian Trojans, simulations of hypothetical objects have indicated that at small sizes (<1 km), the Yarkovsky effect could impact the stability of the objects (Wang & Hou 2017;Hellmich et al 2019). As we are simulating known Jovian Trojans, the majority of the objects are greater than several kilometres in size (Emery et al 2015), and have unknown or highly uncertain thermal properties (Slyusarev & Belskaya 2014;Sharkey et al 2019). For these reasons, we have not included the Yarkovsky effect in our simulations.…”
Section: E T H O D Smentioning
confidence: 99%
“…In all models, a single grain size for all materials is assumed. As with Sharkey et al (2019), we find that allowing for unique grain sizes for each component produces model degeneracies and slows convergence without improving fits. We adopt a single grain size bounded over the range of 0.5-1000 µm.…”
Section: Modeling Approachmentioning
confidence: 64%
“…In this data set, that means fitting band shapes, centers, depths, and the continuum. To determine what physical constraints our data can place on Nereid's surface properties, we utilize the Markov-chain Monte Carlo (MCMC) Hapke modeling methodology after Sharkey et al (2019), which utilizes the emcee python package (Foreman-Mackey et al 2013) and makes use of methodologies developed by Emery & Brown (2004) and Emery et al (2011) for interpreting models of featureless asteroid spectra. Our aim is to explore the types of materials which constitute plausible analogs to a given surface.…”
Section: Modeling Approachmentioning
confidence: 99%
“…The observations followed the procedure of Kareta et al 2018, whereby observations of the target were 'bookended' by observations of a local G-type star for immediate telluric correction and later slope-corrected further using a wellcharacterized solar analog G2V star (SAO 93936) observed near-zenith. This method has been used to effectively and reproducibly characterize faint Solar System small bodies on many occasions (see, e.g., Sharkey et al 2019. ) The reduction was performed partially within the 'spextool' environment (Cushing et al 2004) and partially within custom-written scripts in Python (see 'Software' after the Acknowledgements section).…”
Section: Near-infrared Observations Of 2005 Udmentioning
confidence: 99%